Analisis Perbandingan Kinerja Keuangan Pada Perusahaan Bidang Otomotif Periode Tahun 2019-2023 - Stefani Sindita Sari; Intan Pandini; Astri Ayu Pramesti; Nadia Fransiska Dewi; Febrianti Novita; Cholis Hidayati (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to analyze and compare the financial performance of five automotive companies in Indonesia during the period 2019–2023. The five companies analyzed are PT. Indomobil Sukses Internasional Tbk, PT. Garuda Metalindo Tbk, PT. Mitra Pinasthika Mustika Tbk, PT. Astra Internasional Tbk, and PT. Indospring Tbk. The approach used in this study is qualitative descriptive, with data collected through documentation of annual financial reports from 2019 to 2023 and related literature studies. Data analysis was carried out by calculating financial ratios for each company and year, and comparing performance between companies in the same period. The results of the study show significant variations in the financial performance of companies, where some companies show good stability and efficiency, while others face challenges that require improvements in operational policies and financial management strategies. These findings provide important insights for decision making by stakeholders in the automotive industry.